Low thyroid‐stimulating hormone and its persistence beyond the first trimester of pregnancy. Issue 3 (22nd June 2018) - Fraenkel, Merav; Shafat, Tali; Cahn, Avivit; Erez, Offer; Novack, Victor; Tsur, Anat
Abstract: Objective: To investigate predictors of low thyroid‐stimulating hormone (TSH) persisting beyond the first trimester and associated pregnancy outcomes. Methods: We retrospectively assessed the association between low first‐trimester TSH and obstetric outcomes of singleton pregnancies in southern Israel between 2001 and 2011. We included women with first‐trimester TSH and at least one other THS measurement. Clinical data were from maternity and community medical records. Results: Among 3761 women, 185 (4.9%) had a TSH of 0.10 mIU/L or less in the first trimester. Multiple of the median human chorionic gonadotropin was higher in women with TSH of 0.40 mIU/L or less versus 0.41–4.0 mIU/L, but was not associated with higher rates of persistent low TSH. Maternal age (odds ratio [OR] 1.08, 95% confidence interval [CI] 1.00–1.16; per yearly increment), free thyroxine (FT4; OR 1.11, 95% CI 1.03–1.20; per ng/dL increment), and TSH of 0.10 mIU/L or less (OR 3.06, 95% CI 1.38–6.80 vs 0.21–0.40 mIU/L) were independent predictors of persistent low TSH. No adverse pregnancy outcomes occurred in women with low first‐trimester TSH. Conclusions: Low TSH persisting beyond the first trimester was more common with increasing maternal age, elevated FT4, and TSH below 0.10 mIU/L, but was not associated with obstetric complications. Abstract : Older maternal age, higher thyroxine levels, and thyroid‐stimulating hormone (TSH) levels of 0.1 mU/L or less were predictors of persistent low first‐trimester TSH.